Zu kulturbedingten Gemeinsamkeiten im phraseologischen Bestand des Deutschen und des Polnischen - Schatte, Czesława (Uniwersytet im. Adama Mickiewicza, 1996)
In this contrastive German and Polish study, the author focuses on the cultural conditioning of similarities in the phraseology of both languages. The purpose of this paper is to show those phraseological similarities in German and Polish which can be explained by the impact of common sociocultural background or by the origin from the common historiocultural sources. The similarities are evident in phraseologisms including expressions for body parts, names of animals, plants and colors, as well as those of biblical origin, in Greek and Latin literature, classic literary world masterpieces of Renaissance and Enlightenment. The article provides numerous examples of phraseology in German and Polish, of which systematic compilation constitutes an essential contribution to contrastive studies and can serve as database for teachers of German.